PENGEMBANGAN BUKU PANDUAN PENGEMASAN SAYUR ORGANIK BAGI SISWA TUNAGRAHITA RINGAN SMALB - Reni Dwi Indrawati,; Sudarsini Sudarsini (Department of Special Education, 2014)
Teachers have obstacles in teaching because it has not had the teaching materials appropriate to the characteristics and needs of students. Characteristics of mild mental retardation students are capable learners, the ability to think concretely and hard thinking, not capable of storing instructions difficult, using simple words and easy to understand, then it requires teachers to develop teaching materials that are innovative, creative, interesting, and contextual. Development of organic vegetable packaging guidebook is intended to produce a product of teaching materials that can assist students in learning activities. This research method is the Research and Development (R & D). The results of this study indicate that the guidebook is valid based on the acquisition scores of the experts are experts teaching materials, materials experts, and prospective users number 84, and effectively used for students with mild mental retardation acquisition score of 85.125%.Guru memiliki hambatan dalam mengajar karena belum memiliki bahan ajar yang sesuai dengan karakteristik dan kebutuhan siswa. Karakteristik siswa tunagrahita ringan yang mampu didik, kemampuan berfikir kongkrit dan sukar berfikir, tidak mampu menyimpan instruksi sulit, menggunakan kata sederhana dan mudah dipahami, maka hal tersebut mengharuskan guru untuk mengembangkan bahan ajar yang inovatif, kreatif, menarik, dan kontekstual. Pengembangan buku panduan pengemasan sayur organik ini bertujuan menghasilkan suatu produk bahan ajar yang dapat membantu siswa dalam kegiatan pembelajaran. Metode penelitian ini menggunakan Research and Development (R&D). Hasil penelitian ini menunjukkan bahwa buku panduan tersebut valid berdasarkan perolehan skor dari para ahli yaitu ahli bahan ajar, ahli materi, dan calon pengguna sejumlah 84, serta efektif digunakan bagi siswa tunagrahita ringan dengan perolehan skor 85,125%.